Opportunities, Challenges, and Capital Market Education Strategies through Social Media - Khoiriah, Rizka Ismi; Maris, Anis Wahyu Intan (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2023)
Social media is becoming a popular channel for influencers to share information and recommendations about investment decisions in the capital market. However, this also creates a risk of misleading advice and investment scams for investors who need more financial literacy. The Indonesia Stock Exchange, social media users, and influencers should collaborate to prevent capital market crime and promote investment education. This study explores the challenges and opportunities of using social media as an alternative to capital market education programs. It also aims to formulate appropriate capital market educational strategies and identify the characteristics of capital market-qualified influencers on social media. We used a qualitative approach with a content analysis method and semi-structured interviews. The research subjects are influencers on social media selected using a purposive sampling method. We propose a strategic management process tailored for effective capital market education through social media based on the research findings. The results of this study provide recommendations for investors to refer to information from qualified influencers and regulators.